1992
DOI: 10.1002/neu.480230906
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of intramuscular nerve branching and synaptogenesis to motoneuron survival

Abstract: The target has been considered for some time to play a major role in allowing neurons to survive the period of naturally occurring cell death. For the motoneurons that innervate the chick limb, evidence is presented that suggests access to target-derived trophic factor via intramuscular nerve branches and synapses may be important in regulating neuronal survival. Alterations in branching and synapse formation produced by activity blockade as well as by alteration of adhesion molecule function are shown to resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 60 publications
3
40
1
Order By: Relevance
“…The morphological changes in lumbar motoneurons of gephyrin-deficient mice are consistent with previous pharmacological and molecular genetic studies that identify muscle activity as a key regulator of motoneuron development by demonstrating that muscle paralysis correlates with increased motoneuron survival and muscle innervation (Oppenheim et al, 1986(Oppenheim et al, , 1997Landmesser, 1992;Banks et al, 2003). Our contrasting results for respiratory motoneurons are also consistent with a regulatory role of muscle activity, because electrical overstimulation of muscle has been found to cause increased motoneuron death (Oppenheim and Nunez, 1982).…”
Section: Skeletal Muscle Activity Regulates Motoneuron Development Insupporting
confidence: 89%
“…The morphological changes in lumbar motoneurons of gephyrin-deficient mice are consistent with previous pharmacological and molecular genetic studies that identify muscle activity as a key regulator of motoneuron development by demonstrating that muscle paralysis correlates with increased motoneuron survival and muscle innervation (Oppenheim et al, 1986(Oppenheim et al, , 1997Landmesser, 1992;Banks et al, 2003). Our contrasting results for respiratory motoneurons are also consistent with a regulatory role of muscle activity, because electrical overstimulation of muscle has been found to cause increased motoneuron death (Oppenheim and Nunez, 1982).…”
Section: Skeletal Muscle Activity Regulates Motoneuron Development Insupporting
confidence: 89%
“…Moreover, in embryos continuously exposed to nicotine until 120 hpf, the axons of secondary motoneurons are also severely stunted (data not shown). These results are in stark contrast to the anatomy of motoneurons of zebrafish paralytic mutants, in which motoneuron axons appear normal, and to motoneurons of the developing chick, in which the axons are actually hyperbranched when muscle activity is blocked (Pittman and Oppenheim, 1979;Westerfield et al, 1990;Landmesser, 1992;Ono et al, 2001). This provides yet another line of evidence suggesting a neuronal mechanism for the action of nicotine in embryonic/ larval zebrafish.…”
Section: Nicotine Alters Axonal Pathfinding In Zebrafish Embryos: a Ncontrasting
confidence: 76%
“…However, the fact that both large-and smallsized facial MNs were retrogradely labeled indicates that the rescued MNs must have axons in close proximity to the whiskerpad muscles and that even the small-sized axons have an intact retrograde transport system. It is interesting that whereas the complete rescue of MNs from developmental PCD by neuromuscular activity blockade in avian and mammalian embryos results in a striking increase in intramuscular axon branching and synapse numbers (Landmesser, 1992;Misgeld et al, 2002;Brandon et al, 2003), this was not the case in Bax KO/or MyoGDNF embryos (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies of motor systems developing with reduced PCD have reported more cell bodies in central motor nuclei or more axons in cranial or spinal roots , but with the exception of paralytic chicks and mice (Ding et al, 1983;Oppenheim and Chu-Wang, 1983;Landmesser, 1992;Misgeld et al, 2002), whether rescued MNs project to their muscle targets has not been systematically examined Jacob et al, 2005). In cross sections of adult peripheral hindlimb and cranial nerves (mixed motor and sensory) of Bax KO and MyoGDNF mice (and in the paralyzed embryonic chick), we observed more (Ïł 40 -50%) myelinated axons in close proximity to their muscles compared with WT mice or vehicle-treated chick embryos (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation